The disappeared - Echlin, Kim (Abacus, 2009)
After more than 30 years Anne Greves feels compelled to break her silence about her first lover, and a treacherous pursuit across Cambodia's killing fields. Once she was a motherless girl from taciturn immigrant stock. Defying fierce opposition, she falls in love with Serey, a gentle rebel and exiled musician. She's still only 16 when he leaves her in their Montreal flat to return to Cambodia And, after a decade without word, she abandons everything to search for him in the bars of Phnom Penh, a city traumatized by the Khmer Rouge slaughter. Against all odds the lovers are reunited, and in a political country where tranquil rice paddies harbour the bones of the massacred, Anne pieces together a new life with Serey. But there are wounds that love cannot heal, and some mysteries too dangerous to know. And when Serey disappears again, Anne discovers a story she cannot bear. Haunting, vivid, elegiac, The Disappeared is a tour de force; at once a battle cry and a piercing lamentation, for truth, for love.